2014
DOI: 10.1002/asna.201412067
|View full text |Cite
|
Sign up to set email alerts
|

The interstellar medium and star formation in nearby galaxies

Abstract: In this overview article we present some of the key projects we pursue in our Emmy Noether group. Our work is focused on nearby galaxies, where we use multi-wavelength, state-of-the-art survey data to probe distribution, abundance and properties of gas and dust in the interstellar medium (ISM) on ∼ kpc scales. We study the average, radial distributions of atomic (H I) and molecular hydrogen (H2) across the disks of spiral galaxies and assess local (on 1 kpc scales) correlations between H I, H2 and star formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 62 publications
3
6
0
Order By: Relevance
“…Bigiel et al (2014) identify clear inflow signatures form their study of HI velocity fields for NGC 2403, 3198, 2903, 7331, for which we also determine significant rates of mass infall (see also de Blok et al 2014). Bigiel et al (2014) also detect infall for NGC 6946. We note that while our fit for NGC 6946 finds a solution with Λ = 0 as the best value, the shape of the isocontours in Fig.…”
Section: Discussion and Summarysupporting
confidence: 58%
See 1 more Smart Citation
“…Bigiel et al (2014) identify clear inflow signatures form their study of HI velocity fields for NGC 2403, 3198, 2903, 7331, for which we also determine significant rates of mass infall (see also de Blok et al 2014). Bigiel et al (2014) also detect infall for NGC 6946. We note that while our fit for NGC 6946 finds a solution with Λ = 0 as the best value, the shape of the isocontours in Fig.…”
Section: Discussion and Summarysupporting
confidence: 58%
“…Red filled circles refer to the metallicities given in Table 1 Λ as high as 0.4. For NGC 925, Bigiel et al (2014) find no signs of inflows but instead significant outflows. With η = 0.67 and Λ = 0.54, we detect in NGC 925 both outflows and inflows, but the inflow rate within 3σ can still be consistent with zero (Fig.…”
Section: Discussion and Summarymentioning
confidence: 82%
“…More recent studies on local scales have considered another explanation, again suggesting that the low-density threshold may simply result from the multi-phase ISM. In this picture, the low-density turnover is a phase transition below which the ISM becomes predominantly atomic gas, producing a steep, near-vertical star formation law (e.g., Leroy et al 2008Leroy et al , 2013bBigiel et al 2014). Both the gravitational stability and phase transition models may explain our observed low-Σ gas threshold.…”
Section: Low-density Thresholdmentioning
confidence: 83%
“…On global scales, K98 found that SFR correlates strongly with total gas surface density, moderately with atomic gas surface density (Σ HI ), and only weakly with molecular gas surface density (Σ H2 ). Most of the spatiallyresolved studies, on the other hand, find that SFR correlates most strongly with Σ H2 and almost not at all with Σ HI (e.g., Kennicutt et al 2007;Bigiel et al 2008;Leroy et al 2008;Bigiel et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Observations of high redshift (z>1) galaxies suggest that the gas depletion time scales are < ∼ 1 Gyr (Tacconi et al 2013;Genzel et al 2015;Schinnerer et al 2016;Tacconi et al 2017). Locally gas depletion timescales are much longer, about 1-3 Gyr (Leroy et al , 2013Bigiel et al 2014). These gas depletion timescales are defined relative to the H 2 content of the galaxies and not the total gas content as we have done.…”
Section: Placing Our Model On the Schmidt-kennicutt Lawmentioning
confidence: 99%